ANALISIS SISTEM PENYELENGGARAAN MAKAN SMA NEGERI KHUSUS OLAHRAGA (SMANKOR) PAPUA - Yohanis M Mandosir; Evi Sinaga (University of Cenderawasih, 2017)
Achievement of maximum sports achievement is an integrated process involving various aspects and disciplines, including the availability and quality of facilities and infrastructure, human resources, To improve the performance of Indonesian athletes in the future, especially the achievements of young athletes of Papua, it is necessary to improve and improve the system of training and training of sports including the nutritional status of students / young athletes by first ensuring the adequacy of student food intake begins by looking at the implementation of the meal. This research will analyze the food administration system at SMANKOR Papua in hopes to give description about the implementation and achievement of the program and its impact on the intake and nutritional status of the students Based on the above background, it is seen that the implementation of food implemented by the institution will have an impact on the fulfillment of nutritional intake which is a basic requirement for juvenile athletes to perform daily activities and sports and ultimately will affect the achievement achievement causing researchers interested in conducting analysis of food administration system SMANKOR Papua.. Based on the results of research and data analysis results that have been done, can be obtained: 1) The number of food processing personnel is ideal because students who served amounted to 135 people; (2) The implementation of food generally works well, except on processing because sometimes the menu is presented not in accordance with the master menu, and (3) Menu changes is done after communication with the school and the menu replaced still meet the nutritional needs of school children.